(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Histomorphological changes of epididymis and ductus deferens in male Black Bengal goat due to arsenic were studied. A total of 12 male Black Bengal goats, in which 6 were collected from arsenic affected areas of Mymensingh district and another 6 were collected from hill tracts of Chittagong which were arsenic free.The goats were sacrificed by piercing carotid artery and the samples (Epididymis and Ductus deferens) were collected immediately. Samples were prepared and stained with haematoxylin and eosin stain technique to study the histology under light microscope. In the morphological study, measurement of length, width, breadth and weight of epididymis and ductus deferens were observed. The gross study revealed that there were slight variations in the gross morphology of epididymis and ductus deferens of arsenic affected Black Bengal goat, but this variation was statistically insignificant. In the histological study, arsenic affected goat showing increased thickness of epididymal covering (P<0.05) and trabeculae compared to control group of epididymis. The diameter of ductule efferentes of arsenic affected goat was narrower (P<0.01), width between intertubular space of ductuli efferentes was wider (P<0.01), lumen of ductules contain smaller in amount of spermatozoa compared to control group. The wall of the ductus deferens was thicker in arsenic affected goats than the control group (P<0.01). It may be concluded that environmental health hazard of arsenic might have adverse effects on the male reproductive organs. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18220 J. Bangladesh Agril. Univ. 11(1): 103-110, 2013